1988
DOI: 10.1093/ptj/68.12.1840
|View full text |Cite
|
Sign up to set email alerts
|

Pathomechanics of Structural Foot Deformities

Abstract: This article presents the most common structural foot deformities encountered in clinical practice. The deformities are defined, and the expected compensations at the subtalar joint (STJ) are described. The theoretical consequences of the STJ compensations on proximal and distal tissues are presented. A biomechanical rationale for certain tissue disorders is described. The possible effects of abnormal STJ compensation on osseous development are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
102
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 11 publications
5
102
1
1
Order By: Relevance
“…The concern is that patients undergoing TKA, who also present with a stiff subtalar joint, may have subsequent, post-TKA foot/ankle pain or disability resulting from the inability of the subtalar joint to reorient itself after knee realignment (Fig. 7) [16]. Patients undergoing TKA who also have stiff subtalar joints, on preoperative examination, should be counseled that their hindfoot symptoms might worsen after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The concern is that patients undergoing TKA, who also present with a stiff subtalar joint, may have subsequent, post-TKA foot/ankle pain or disability resulting from the inability of the subtalar joint to reorient itself after knee realignment (Fig. 7) [16]. Patients undergoing TKA who also have stiff subtalar joints, on preoperative examination, should be counseled that their hindfoot symptoms might worsen after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…The term ligamentous creep refers to stretching and decreased strength in ligaments caused by continuous stresses on them, which in turn causes instability of the forefoot during weightbearing. 15 Numerous reasons for such structural foot changes can be postulated: 1) biomechanical deformity (pes planus), 2) a hormonal cause of excessive mass (eg, increased height seen in subjects with excessive body mass), 3) an excess of adipose tissue, 4) increased bone formation and subperiosteal expansion resulting from increased plantar forces and pressures experienced during gait, and 5) a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been extensively debated in literature for managing pediatric disorders through controlling the foot structure of the children [31][32][33][34]. The essence of foot orthoses is the emphasis of the importance of dynamic inter-relationships of foot joints during gait [15,23,[35][36][37]. The biomechanical principles in which foot orthoses work remain contentious [38][39][40][41].…”
Section: Foot Orthotic Interventionmentioning
confidence: 99%
“…The biomechanical principles in which foot orthoses work remain contentious [38][39][40][41]. However, previous systematic reviews revealed favourable therapeutic outcomes when foot orthoses are prescribed to manage abnormal foot pronation and its associated pathological conditions [16][17][18]36] with high levels of efficacy [19,20] and patient's satisfaction [21].…”
Section: Foot Orthotic Interventionmentioning
confidence: 99%